2018
DOI: 10.1093/jee/toy021
|View full text |Cite
|
Sign up to set email alerts
|

Does Soil Treated with Conidial Formulations of Trichoderma spp. Attract or Repel Subterranean Termites?

Abstract: Previous studies showed that many wood-rotting fungi were attractive to termites; however, little attention has been paid to the relationship between termites and soil fungus. In the present study, different designs of two-choice tests were conducted to investigate the behaviors of two subterranean termites, Coptotermes formosanus Shiraki (wood-feeding lower termites) and Odontotermes formosanus (Shiraki) (fungus-growing higher termites), in response to soil (or sand) treated with the commercial conidial formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…In general, Trichoderma fungi inhibited the tunneling activities of the fungus-growing higher termite, Odontotermes formosanus (as shown in the present study), and they are antagonistic to the Termitomyces cultured by fungus-growing termites [24]. On the contrary, Trichoderma fungi attract the wood-feeding lower termite, Coptotermes formosanus [29], and benefit this termite by antagonizing the entomopathogenic fungi and cellulose-competition fungi [50,51].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In general, Trichoderma fungi inhibited the tunneling activities of the fungus-growing higher termite, Odontotermes formosanus (as shown in the present study), and they are antagonistic to the Termitomyces cultured by fungus-growing termites [24]. On the contrary, Trichoderma fungi attract the wood-feeding lower termite, Coptotermes formosanus [29], and benefit this termite by antagonizing the entomopathogenic fungi and cellulose-competition fungi [50,51].…”
Section: Discussionsupporting
confidence: 72%
“…Although Trichoderma fungi are not pathogenic to termites, they antagonize Termitomyces cultured by the fungus-growing higher termites. Our previous work showed that commercially formulated conidia of T. viride repelled tunneling behavior of O. formosanus [29]. In the present study, we found that unformulated conidia of six Trichoderma fungi significantly decreased the tunneling behaviors of O. formosanus ( Table 2), indicating that O. formosanus showed general avoidance behaviors in response to different fungal species in the genus Trichoderma.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Suran and Rust [22] reported that 3% xylose in the food (paper discs) significantly increased the intake and horizontal transfer of hexaflumuron among individuals of Reticulitermes hesperus Banks, and caused significantly higher termite mortality than that of hexaflumuron alone. Other reported termite attractants include wood-rotting and soil fungi [23][24][25][26][27], decayed wood extract [28], carbon dioxide [29,30], clay materials [11,31,32], and even some sport drinks [33].…”
Section: Discussionmentioning
confidence: 99%